Optimization for preparing Bi1.68Pb0.32Sr1.75Ca1.85Cu2.85O10+y powders by wet ball milling. (1st June 2022) - Chen, Yingwei; Shao, Ling; Zhao, Guomeng; Liu, Qijie; Huang, Yingqi; Liu, Zhenzhong; Zhu, Liu; Wang, Tianle; Zheng, Beibei
Abstract: Superconducting Bi1.68 Pb0.32 Sr1.75 Ca1.85 Cu2.85 O10+ y (Bi-2223) powders were prepared by a conventional solid-state reaction using hand grinding and wet ball milling. The effects of the ball milling and sintering times on the phase evolution were examined by x-ray diffraction and magnetic susceptibility measurements. Single-phase Bi-2223 powders with a superconducting transition temperature of about 108 K were optimally prepared by wet ball milling for 20 h and sintering at 867 °C for 80 h. Finding these optimal preparation conditions were crucial for mass producing high-quality single-phase Bi-2223 precursor powders with a much lower cost of energy. Furthermore, we found that ball milling led to thinner grains than hand grinding.